Between popes, inquisitors and princes : how the first Jesuits negotiated religious crisis in early modern Italy - Dalton, Jessica M. (St. Andrews studies in Reformation history., 2020)
In Between Popes, Inquisitors and Princes Jessica Dalton uses extensive, original archival research to provide the first history of a unique and controversial papal privilege that allowed the first Jesuits to absolve heretics in sixteenth-century Italy without involving bishops or inquisitors. Dalton uses the story of this remarkable privilege to reconsider two central aspects of Jesuit history: their role in the Counter-Reformation and their relationship with the papacy. Dalton convincingly argues that, in the aftermath of the Protestant Reformation, the Jesuits were valued collaborators of popes, inquisitors and princes not for their obedience and subservience but rather because they worked with an autonomy and flexibility that allowed them convert heretics where political barriers and popular hostility hindered inquisitors and prelates.